Construction and validation of the investigative skills scale for university students (Revista Innova Educación, 2023)
Investigative skills are essential for proper development at the higher level. The objective of the study was to build a scale aimed at measuring investigative skills, as well as to determine the level of said skills in university students in the city of Piura, Peru. The study was of a non-experimental, instrumental, simple descriptive design, the research had the participation of 1682 students. At the instrumental level, adequate indicators of content, construct and convergence validity were found, as well as adequate reliability and rating indices. At a descriptive level, a predominance of the low level (60.7%) was found, followed by a medium level (30.3%) and a high level (9.0%). In the 7 underlying domains, a predominance of the low level was found in more than 50% of the population. In conclusion, an ideal instrument was obtained for the optimal measurement of the construct. After its application, it was found that the level of investigative skills and their underlying components predominate at a low level.
Keywords: ability; education; factorial analysis; research; psychometry